Transformational Leadership and Teacher Performance in Islamic Schools: A Structural Equation Modelling Approach in the Era of Educational Disruption - Waryadi Waryadi; Cecep Sumarna; Abdul Karim; Nur Muhammad Iskandar; Ahmad Zaldi (Sakura Digital Nusantara, 2026)
Purpose: This study aims to examine how transformational leadership contributes to enhancing teachers’ inventiveness and creativity in madrasah environments, as part of efforts to improve educational quality in times of rapid change. Method: This research employs a quantitative approach using a questionnaire as the primary data collection instrument. The collected data were analyzed using structural equation modeling (SEM). Findings: The results indicate that transformational leadership plays a significant role in fostering supportive relationships and increasing teacher motivation, which subsequently encourages more inventive and creative performance among teachers. Research Implication: This study highlights the importance of implementing transformational leadership practices to cultivate a culture of creativity and innovation, thereby improving teacher productivity and overall educational quality. Originality: This study contributes by examining the link between transformational leadership and teacher creativity in madrasah contexts, supported by SEM-based empirical evidence.